Performance of Sapota-Teak based agroforestry system in hill zone of Karnataka - Patil, S.J.; Mutanal, S.M.; Patil, H.Y.; Shahapurmath, Girish; Maheswarappa, V. (Indian Journal of Agroforestry, 2020)
A long-term agroforestry experiment consisting of arable crops (Paddy, maize, sunhemp). Silvicultural trees viz., Eucalyptus tereticomis, Casuarina-equisetifolia. Albizia molucana, Tectona grandis, Dalbergia sissoo, horticultural tree (sapota) and pasture crop (guinea grass) was initiated on black clayey soils at Prabhunagar (Dharwad) during 1976. Sapota (Achras sapota) was planted at 10 m apart and three tree species were planted in between 2 Sapota plants. Guinea grass (Panicum maximum) slips were planted on either side of sapota and tree species in a small strip of 1 m width. At the end of 17 years (felling all short rotation trees and only adjoining long rotation trees), economic analysis indicated that, benefit cost ratio and internal rate of returns were highest in agroforestry system with T. grandis (1.67: 1 and 23.2%, respectively) and were lowest in sapota+C. equisetifolia (0.99: 1 and 12%, respectively). The economic analysis at the end of 28 years (felling trees) indicated that benefit cost ratio was higher in sapota+T. grandis+field crops (3.23: 1) followed by sapota+Lagerstroemia lanceolata+field crops (2.71:1) and sole sapota (2.36:1). This teak based agroforestry model is economically viable agroforestry system.